8.8k views
2 votes
How do i simplify this as much as possible

6(√a³b²c⁴)/9b√ac³

User BigMike
by
5.6k points

1 Answer

6 votes

Answer:
(2a√(c))/(3)

Explanation:

Remember that:


  • \sqrt[n]{a^n}=a

  • √(ab)=(√(a))(√(b))

  • (√(a))^2=a
  • The product of powers property establishes that:
    (a^m)(a^n)=a^((m+n))

Given the expression
(6(√(a^3b^2c^4)))/(9b√(ac^3) )

You know that:


a^3=a^2*a\\c^3=c^2*c

Then, you must rewrite the expression and simplify:


(6√(a^2ab^2c^4))/(9b√(ac^2c) )=(6abc^2√(a))/(9bc√(ac))=(2ac√(a))/(3(√(a))(√(c)))=(2ac)/(3√(c))

Multiply the numerator and the denominator by
√(c):


((2ac)√(c)))/((3√(c))(√(c)))=(2ac√(c))/(3(√(c))^2)=(2ac√(c))/(3c)=(2a√(c))/(3)

User Hatcat
by
5.9k points